2013
DOI: 10.1371/journal.ppat.1003345
|View full text |Cite
|
Sign up to set email alerts
|

Class A Scavenger Receptor 1 (MSR1) Restricts Hepatitis C Virus Replication by Mediating Toll-like Receptor 3 Recognition of Viral RNAs Produced in Neighboring Cells

Abstract: Persistent infections with hepatitis C virus (HCV) may result in life-threatening liver disease, including cirrhosis and cancer, and impose an important burden on human health. Understanding how the virus is capable of achieving persistence in the majority of those infected is thus an important goal. Although HCV has evolved multiple mechanisms to disrupt and block cellular signaling pathways involved in the induction of interferon (IFN) responses, IFN-stimulated gene (ISG) expression is typically prominent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 58 publications
1
72
0
Order By: Relevance
“…However, HSV-1 is well-known for its extensive ability to suppress immunity in cells that it infects (Melchjorsen et al, 2009), so SIDT2-mediated bystander activation – whereby uninfected host cells take up, detect, and respond to extracellular HSV-1 dsRNA released from infected cells – may represent an important counter strategy for host immunity. Along similar lines, recent in vitro experiments have demonstrated a role for dsRNA-based activation of bystander cells in limiting hepatitis C virus (HCV) infection (Dansako et al, 2013), but our results provide evidence that this activation is important in vivo and highlight a physiological role for extracellular RNA at a time when this is a matter of considerable interest and debate (Leslie, 2013). …”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, HSV-1 is well-known for its extensive ability to suppress immunity in cells that it infects (Melchjorsen et al, 2009), so SIDT2-mediated bystander activation – whereby uninfected host cells take up, detect, and respond to extracellular HSV-1 dsRNA released from infected cells – may represent an important counter strategy for host immunity. Along similar lines, recent in vitro experiments have demonstrated a role for dsRNA-based activation of bystander cells in limiting hepatitis C virus (HCV) infection (Dansako et al, 2013), but our results provide evidence that this activation is important in vivo and highlight a physiological role for extracellular RNA at a time when this is a matter of considerable interest and debate (Leslie, 2013). …”
Section: Discussionsupporting
confidence: 70%
“…To circumvent this inhibition, infected cells can transfer viral dsRNA extracellularly to uninfected bystander cells, thereby promoting IFN-I production and limiting viral replication in vitro (Dansako et al, 2013). How such transfer occurs is yet to be determined, and the importance of this transfer to immunity in vivo – while postulated – remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Additional HCV PAMPS for TLR3 could come following uptake of HCV RNA from the extracellular milieu (possibly from dying infected cells) by scavenger receptors or through autophagic processes. 62; 63 This uptake could lead to viral PAMP presentation to TLR3 in the endosome in uninfected cells setting up an antiviral state even in uninfected hepatocytes. HCV sensing by TLR7 occurs in both plasmacytoid dendritic cells (pDCs) and Kupffer cells, leading to production of IFN or activation of the inflammasome (Fig.…”
Section: How Is Hcv Sensed As Non-self?mentioning
confidence: 99%
“…The most studied SRs are SRA and B. SRA recognizes Gram-positive bacteria via binding to Lipoteichoic acid (LTA) [9]. Studies also showed that SRA could restrict hepatitis C virus replication by interacting with TLR3 in human hepatocytes [10]. CD36, which is the first cloned class B SR, is a sensor for LTA and diacylated lipopeptide, as well as a co-receptor for TLR2 in responses to microbial diacylglycerides [11].…”
Section: Introductionmentioning
confidence: 99%